PENINGKATAN PENGETAHUAN MITIGASI BENCANA SISWA SEKOLAH DASAR DI AREA GUNUNG SEMERU - Guruh Wirasakti; Yunita Wahyu Wulansari; Nur Khoiriyah (LPPM Universitas dr. Soebandi, 2024)
Knowledge about natural disaster mitigation is an obstacle in disaster risk management efforts in various regions. Limited communities living in disaster-prone areas still lack adequate knowledge and training on how to reduce the impact of disasters. Children who should receive basic information about disaster mitigation, often do not get knowledge related to disaster mitigation. The purpose of community service is to increase students' knowledge about disaster mitigation of Mount Semeru so as to build a community that is responsive to disasters. The activity implementation mechanism is divided into three stages, namely preparation, implementation, and evaluation. The results of community service are before health education on disaster mitigation of Mount Semeru, the majority of elementary school students have less knowledge related to disaster mitigation, namely 54 students or 83%. However, after being given knowledge about Mount Semeru Disaster Mitigation, student knowledge increased to 48 students or 74% good. Community service activities to increase the disaster mitigation knowledge of elementary school students in the Mount Semeru area can increase the disaster mitigation literacy of elementary school students to increase. Elementary school students can recognise and identify the threat of volcanic eruption, understand the status of early warning, and actions taken during pre-disaster.